2021
DOI: 10.1111/conl.12842
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging shark‐fin consumer preferences to deliver sustainable fisheries

Abstract: At least one third of sharks and their cartilaginous relatives (Class Chondrichthyes) meet the IUCN Red List Criteria for being threatened with extinction. Overfishing is the primary threat, with less than 4% of the world's shark catches managed for sustainability. The high-value shark-fin trade has gained the greatest attention as a conservation issue, yet there has been little research on shark-fin consumer preferences, and how these might be leveraged to deliver sustainability goals. We used an online discr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…Understanding stock sustainability is a required first step to tackle this threat; however, interventions to promote sustainability and reduce overexploitation need to consider consumers and the decisions they make to change unsustainable behaviours (Zhou et al, 2021).…”
Section: Con Sumer Choice and S Hark Sus Tainab Ilit Ymentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding stock sustainability is a required first step to tackle this threat; however, interventions to promote sustainability and reduce overexploitation need to consider consumers and the decisions they make to change unsustainable behaviours (Zhou et al, 2021).…”
Section: Con Sumer Choice and S Hark Sus Tainab Ilit Ymentioning
confidence: 99%
“…Overexploitation threatens many shark species worldwide. Understanding stock sustainability is a required first step to tackle this threat; however, interventions to promote sustainability and reduce overexploitation need to consider consumers and the decisions they make to change unsustainable behaviours (Zhou et al, 2021). Understanding the human dimensions of sharks is considered critical for the success of conservation and management initiatives (Simpfendorfer et al, 2011).…”
Section: Consumer Choice and Shark Sustainabilitymentioning
confidence: 99%
“…One study in China found that consumers generally prefer higher priced and rarer shark fins, which reinforces the notion that shark fin is consumed as a luxury goods (Zhou et al, 2021). As such, fins are often sold at US$200-400 per kg, and sometimes up US$1000 per kg (Clarke, 2004;Southeast Asian Fisheries Development Center, 2006).…”
Section: Introductionmentioning
confidence: 81%
“…It has been traditionally served as a signal of power in Chinese folk custom and is believed to provide tonic health benefits to consumers (Clarke et al., 2007; Dell'Apa et al., 2014; Fabinyi, 2012). This dish is usually served at important corporate or social banquets as a prestigious item believed to embody wealth, hospitality and social status; and thus reinforce relationships among people (Dell'Apa et al., 2014; Zhou et al., 2021). One study in China found that consumers generally prefer higher priced and rarer shark fins, which reinforces the notion that shark fin is consumed as a luxury goods (Zhou et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The discrete choice experiment (DCE) is considered as a well‐established method to explore stated preference (Johnston et al, 2017), which has been widely used in consumer decision‐making trade‐offs in sustainability science (Byun et al, 2018; Natali et al, 2022; Tait et al, 2019; Zhou et al, 2021). The experiments required the respondents to compare and weigh the specific choices (or products) according to different characteristics of their attributes.…”
Section: Methodsmentioning
confidence: 99%